Internationalization of Cold War systems analysis: RAND, IIASA and the institutional reasons for methodological change. (October 2016) - Duller, Matthias
This article has a dual purpose. First, it looks at the transfer of the methodology of systems analysis from the RAND Corporation to the International Institute for Applied Systems Analysis (IIASA) in the wake of an East–West bridge-building effort during the Cold War. Second, it draws out a more general argument about how the institutional structures of these research organizations condition their methodological orientations. Acknowledging the complexity of factors influencing methodological choices at RAND and IIASA, the article concentrates on the centrality of institutional purpose, institutional environments and internal organizational structure, and demonstrates how, when taken together, these factors led to a methodological diversification at IIASA that is best summarized as the internationalization of systems analysis.